Incidence and Non â Pharmacological Management of Dysmenorrhea - Ernald Zeqja, Alma Imami LelÃƒÂ§aj, Robert Qirko, (Journal of Medical Biomedical and Applied Sciences, 2016)
Aim: The aim of this study is to determine the prevalence of primary dysmenorrhea, its impact in life quality also non-pharmacological treatment methods.Â Method: This was a cross sectional study conducted in 2015. In this study participated 320 female students of the Faculty of Technical Medical Sciences, University of Medicine, Tirana, Albania. For the data collection was used a questionnaire.Â Results: The prevalence of primary dysmenorrhea was 85%. The severity of pain referred by students was: 50% moderate pain, 34% severe pain, and 16% mild pain. 51% of students donât use drugs to relieve the menstrual pain, while 49% use painkiller. The medications used to treat or reduce the symptoms of dysmenorrhea were: 43% Acetaminophen, 41% Ibuprofen, 9% Mefenamic acid, 6% Aspirin and 2% Naproxen. Over 86% females included in this study, use self-management strategies for menstrual pain. Among the most used non-pharmacological strategies of self-management to reduce the pain were: sleeping 54 %, resting 47.4%, lie on oneâs stomach 37.1 %, wearing loose garments 34.5 %, etc. Also resulted that the most affected activity by the dysmenorrhea were: concentration during classes 76.8%, daily activity 75.7%, and relations with friends 51.8%, social activity 50%, the family relationship 47.8%, test results 45.9%, school attendance 41.5% and participation in exams 23.5%.Conclusions: Dysmenorrhea and accompanying symptoms have a negative impact on a significant number of students by influencing their physical, social and the academic activity. Non-pharmacological methods should be promoted more and more because they are easy to use, cost effective and without adverse collateral effects.